GAMBARAN PERILAKU ALTRUISME GURU BIMBINGAN DAN KONSELING SMP DI KABUPATEN PASURUAN - Fatma Risyala; Lely Ika Mariyati (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
The purpose of this study was to find out the description of the altruistic behavior of the junior high school guidance and counseling teachers in Pasuruan Regency which is based on the existence of altruistic behavior problems of the junior high school guidance and counseling teachers in Pasuruan Regency. This research is a quantitative research with a descriptive design, to provide an overview of a symptom or phenomenon regarding the altruistic behavior of counseling teachers. The sampling technique in this study used the Issac & Michael table at an error rate of 5% of the Counseling Teacher population with a sample of 105 teachers from a total population of 146 teachers. Data analysis to test the assumptions in this study used the Pearson product moment correlation with the help of the JASP program version 0.16 for windows. The results in this study showed that 80% of the altruistic behavior of counseling guidance teachers was classified as moderate and 20% was classified as low and the aspect that dominated their altruistic behavior was the Helper.